How to Conduct an On-farm Dye Test and Use the Results to Improve Drip Irrigation Management in Vegetable Production - Eric Simonne; David Studstill; Michael Dukes; John Duval; Robert Hochmuth; Gene McAvoy; Teresa Olczyk; Steve Olson; Elizabeth Lamb (EDIS)
Improving irrigation management in vegetable crop production reduces production costs, saves water, and reduces the risk of nutrient leaching. As water movement in the root zone below mulched beds is difficult to see, injecting soluble dye through the drip irrigation system provides a simple and practical method to visualize water movement in the soil. Understanding water movement in raised beds is essential for improving irrigation scheduling and nutrient delivery. This document is HS980 one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2004.